UNIT TOTAL COSTS: AN ALTERNATIVE MARGINAL COST PROXY FOR INFLATION DYNAMICS. (28th September 2015) - Bratsiotis, George J.; Robinson, Wayne A.
Abstract : The New Keynesian Phillips curve (NKPC) driven by unit labor costs has been criticized for failing to match inflation dynamics and for failing to explain the duration of price contracts. This paper extends recent attempts in the literature to improve the fit of the NKPC, by introducing a fuller marginal cost proxy, unit total costs, that is derived from both labor and nonlabor unit costs ; the latter include capital-related costs and production taxes. Borrowing costs are examined separately, as in the cost channel literature. Unit total costs are shown to improve the fit of the short-run variation in inflation and strengthen the empirical support for the role of expectations-based inflation persistence. They also imply a duration of fixed nominal contracts that is closer to those suggested by firm-level surveys. The cost channel becomes relatively less important when unit total costs, rather than unit labor costs, are used as a marginal cost proxy.